Experimental investigation of high‑viscosity oil–water flow in vertical pipes: flow patterns and pressure gradient - Ganat, Tarek A.; Ridha, Syahrir; Hrairi, Meftah; Arisa, Juhairi; Gholami, Raoof (Springer, 2019)
Flow experiments have been conducted for two-phase flow in a vertical pipe. The experiments were made for highly viscous oil–water in a stainless pipe at 250 psig pressure through the laboratory-scale flow test equipment. The test section used is a vertical transparent tube of 50 cm length and 40 mm ID. The test fluid utilized in this experiments is synthetic oil (viscosity = 35 mPas, density = 860 kg/m3) and filtered tap water (interfacial tension 31 mN/m at 20 °C, viscosity 0.95 mPas at 25 °C). The measurements of superficial velocities of oil and water were varied between 0.01 to 3 m/s. According to the experimental observations using audiovisual recordings, a flow pattern map was identified at different condition. Measuring the variations in pressure gradient and flow patterns at different superficial velocities of two-phase flow, six typical flow patterns were categorized and mapped under two groups, oil-dominant region and water-dominant region, and categorized based on the variations of oil and water superficial velocities, and mixture fluid velocity, at different amount of the water holdup in the vertical tubing. The measurements of the total pressure gradient at five different mixture fluid velocities were conducted verses water holdup in vertical tubing. The results show that all the upward flows show an identical flow pattern, where the pressure gradients increase with increasing mixture fluid velocity and water cut with similar trend. The experiments show a clear peak in the pressure gradient as a result of the frictional factor, specifically at the point of flow patterns occurs (i.e., water holdup ~ 30%). The results concluded that the pressure gradient is significantly influenced by flow patterns and flow rates. Besides, the oil viscosity has a high effect on the pressure gradients; however, it is observed that at similar water and oil superficial velocities, there is a subsequent increase in the pressure gradient due to the increase in oil viscosity.